ECONOMICAL EFFECTS OF ORGANIC PRODUCTION OF SPELT WHEAT - Вељко Вукоје; Марија Бодрожа-Соларов (Ekonomika Poljoprivrede (1979), 2011)
This paper analyses the costs and results of organic production of spelt wheat. Comparative cost-effectiveness analysis of the most important parameters is based on analytical calculations of organic and conventional production of spelt wheat. The organic cultivation system requires 56.2% higher amount of investments of variable factors of production per hectare than conventional system. Considering lower yields, the price of fnal organic product is higher two times. Organic production brings higher income per unit of capacity (5.2%), but the margine of coverage is signifcantly lower. Nevertheless, the margin of coverage in organic spelt production (113.782 din/ha) is high enough that this production may be assessed as cost-effective. This statement is corroborated by the cost-effectiveness ration (2.24) and accumulation production rate (55.4%) as well.